Diagnosis, management strategies and research horizons in sarcopenia - Sarah Razaq; Murat Kara; Levent Özcakar; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2022)
Sarcopenia was first described by Rosenberg as the agerelated loss of skeletal muscle mass. The early operational definitions of sarcopenia were based on low muscle mass alone. However, research has suggested a strong predictive relationship between measures of muscle quality i.e., strength and/or physical performance, and health outcomes. Therefore, the definition has been revised to "age-related loss of muscle mass and muscle function". The etiology of sarcopenia is multifactorial and diagnostic recommendations published to date have addressed the total or appendicular muscle mass. Measurement of anterior thigh muscle mass has better correlations with functional tests and all-cause mortality when compared with appendicular or total muscle mass measurements. The aim of this review is to highlight the importance of sarcopenia as an emerging public health issue, diagnostic evaluation with muscle mass and functional performance evaluations and appropriate interventions for management. Keywords: Muscle mass, lean mass, geriatrics, rehabilitation intervention, muscle power.